The gynostemium: More than the sum of its parts with emerging floral complexities (2024)
ABSTRACT: Partial or complete floral organ fusion, which occurs in most angiosperm lineages, promotes integration of whorls leading to specialization and complexity. One of the most remarkable floral organ fusions occurs in the gynostemium, a highly specialized structure formed by the congenital fusion of the androecium and the upper portion of the gynoecium. Here we review the gynostemia evolution across flowering plants, the morphological requirements for the synorganization of the two fertile floral whorls, and the molecular basis most likely responsible for such intimate fusion process.